Dictionary poetics : toward a radical lexicography. - Dworkin, Craig Douglas (New York : Fordham University Press, 2020)
Dictionary Poetics analyses book-length poems from a number of writers who have used particular editions of specific dictionaries to structure their work. Authors include Louis Zukofsky , George Oppen, Clark Coolidge, Bernadette Mayer, Tina Darragh, and Harryette Mullen.
Introduction: Toward an Experimental Lexicography -- Funk & Wagnalls Practical Standard Dictionary of the English Language and Louis Zukofsky's Thanks to the Dictionary -- Webster's Collegiate and Louis Zukofsky's The Oxford English Dictionary and George Oppen's Discrete Series -- Webster's New Collegiate and the Poetry of Clark Coolidge and Bernadette Mayer -- The Random House Dictionary of the English Language and the Poetry of Tina Darragh -- Juba to Jive: A Dictionary of African-American Slang and Harryette Mullen's Muse & Drudge.
Includes bibliographical references and index.
JSTOR
Keywords: American poetry -- 20th century -- History and criticism; American poetry -- 21st century -- History and criticism; English language -- Lexicography; Poetics; Creation (Literary, artistic, etc.); Poésie américaine -- 20e siècle -- Histoire et critique; Poétique.; LITERARY CRITICISM / Poetry; American poetry; Creation (Literary, artistic, etc.); English language -- Lexicography; Poetics; 1900-2099; Criticism, interpretation, etc